Solubility enhancement, physicochemical characterization and formulation of fast-dissolving tablet of nifedipine-betacyclodextrin complexes (Brazilian Journal of Pharmaceutical Sciences, 2012)
The main objective of the study was to enhance the dissolution of nifedipine, a poorly water soluble drug by betacyclodextrin complexation and to study the effect of the preparation method on the in vitro dissolution profile. The stoichiometric ratio determined by phase solubility analysis for inclusion complexation of nifedipine with β-cyclodextrin was 1:1. Binary complex was prepared by different methods and was further characterized using XRD, DSC and FT-IR. A saturation solubility study was carried out to evaluate the increase in solubility of nifedipine. The optimized complex was formulated into fast-dissolving tablets by using the superdisintegrants Doshion P544, pregelatinized starch, crospovidone, sodium starch glycolate and croscarmellose sodium by direct compression. Tablets were evaluated for friability, hardness, weight variation, disintegration and in vitro dissolution. Tablets showed an enhanced dissolution rate compared to pure nifedipine.